English ANALISIS KINERJA KEUANGAN ANGGARAN PENDAPATAN DAN BELANJA DITINJAU DARI RASIO KEUANGAN KOTA PEKANBARU - ASSEGAF, ZAKKY HAIKAL; AHYARUDDIN, MUHAMMAD; MARLINA, EVI (Fakultas Ekonomi Universitas Islam Indragiri, 2025)
Local Own-Source Revenue (PAD) is one of the main sources of funding for regional expenditures. The decline in PAD and government performance significantly impacts the financial performance of the Pekanbaru City Government. This study aims to examine the financial performance of the Pekanbaru City Government as assessed by fiscal decentralization ratio, regional independence, efficiency, effectiveness, and harmony ratios. The financial ratios used in this study include the fiscal decentralization ratio, regional dependency ratio, efficiency ratio, effectiveness ratio, and harmony ratio. The data utilized in this research comprise primary data obtained through interviews and secondary data in the form of the financial statements of the Pekanbaru City Government. The study employs the interactive data analysis method by Miles & Huberman. The results indicate that the financial performance of the Pekanbaru City Government, as measured by the fiscal decentralization ratio, tends to be fairly good, while efficiency is classified as highly efficient. However, the effectiveness ratio indicates ineffective financial performance, and the calculation of the independence ratio shows that Pekanbaru's level of dependency is relatively low or consultative. Furthermore, operational expenditures dominate over capital expenditures, which hinders the provision of infrastructure and facilities that support the improvement of public welfare and services in Pekanbaru City.